2023
DOI: 10.1101/2023.02.12.528244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerobic exercise reverses aging-induced depth-dependent decline in cerebral microcirculation

Abstract: Aging is a major risk factor for cognitive impairment. Aerobic exercise benefits brain function and may promote cognitive health in older adults. However, underlying biological mechanisms across cerebral gray and white matter are poorly understood. Selective vulnerability of the white matter to small vessel disease and a link between white matter health and cognitive function suggests a potential role for responses in deep cerebral microcirculation. Here, we tested whether aerobic exercise modulates cerebral m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…This gradation was dampened in aged mice because of reduced flow in deep tissues and increased flow in upper cortex. These findings align with previous reports of both increases 39 and decreases 40 in blood flow with brain aging, and explain how these conditions co-exist, but at different cortical depths. Our observation of age-related capillary dilation in upper cortex is also consistent with prior work.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This gradation was dampened in aged mice because of reduced flow in deep tissues and increased flow in upper cortex. These findings align with previous reports of both increases 39 and decreases 40 in blood flow with brain aging, and explain how these conditions co-exist, but at different cortical depths. Our observation of age-related capillary dilation in upper cortex is also consistent with prior work.…”
Section: Discussionsupporting
confidence: 92%
“…24,49 Similarly, life-style changes such as exercise have also recently been shown to rescue age-related blood flow deficits in the CC. 40…”
Section: Discussionmentioning
confidence: 99%
“…Further, deep two-photon imaging in awake mice showed age-related hypoperfusion was greatest in the callosal white matter 44 . Thus, brain location may be key during studies to relate capillary regression with cerebral blood flow.…”
Section: Discussionmentioning
confidence: 94%
“…However, cortical depth analysis revealed that deeper cortical layers (Layer 5) exhibit more severe capillary rarefaction and is in fact associated with ACT vasoconstriction 42 . Further, deep two-photon imaging in awake mice showed age-related hypoperfusion was greatest in the callosal white matter 43 . Thus, brain location is key during studies to relate capillary regression with cerebral blood flow.…”
Section: Discussionmentioning
confidence: 94%
“…Coupled with less efficient on-demand oxygen delivery, these age-related changes will make deep cortical layers highly vulnerable. There is evidence that exercise can help ameliorate age-related declines in perfusion and oxygenation 107 .…”
Section: Discussionmentioning
confidence: 99%